Mapping the clinical outcomes and genetic evolution of Ebola virus in Sierra Leone - Li, Tao (JCI Insight, 2017)
Sierra Leone was the most severely affected country in Western Africa during the 2013–2016 outbreak of Ebola virus disease (EVD). Previous genome surveillance studies have revealed the origin, diversity, and evolutionary dynamics of the Ebola virus (EBOV); however, the information regarding EBOV sequences is insufficient, especially the clinical outcomes, given that the correlation between the clinical outcomes and the genetic evolution of EBOV is still not clear. Here, we collected and curated a comprehensive data set that includes 514 EBOV genome sequences from patients with confirmed EVD (including 60 sequences not previously studied), >87.5% of which have residence information and definitive clinical outcomes. Phylogenetic reconstruction revealed 11 lineages of EBOV in Sierra Leone. The median-joining haplotype network showed that haplotypes that are associated with lethal outcomes tend to contribute more to the spread of the EBOV in Sierra Leone than those with live outcomes. Analyses of the spatial-temporal distribution unraveled the lineage-distinctive distribution patterns. Different viral lineages have different case fatality rates (CFRs) during the same stage of the outbreak, implying that several lineages featuring SNPs may correlate with increased/decreased CFRs. This study provides invaluable data sets of EBOV infection and highlights the potential SNPs for further in-depth investigation.